2018
DOI: 10.1186/s12864-018-4893-5
|View full text |Cite
|
Sign up to set email alerts
|

The first next-generation sequencing approach to the mitochondrial phylogeny of African monogenean parasites (Platyhelminthes: Gyrodactylidae and Dactylogyridae)

Abstract: BackgroundMonogenean flatworms are the main ectoparasites of fishes. Representatives of the species-rich families Gyrodactylidae and Dactylogyridae, especially those infecting cichlid fishes and clariid catfishes, are important parasites in African aquaculture, even more so due to the massive anthropogenic translocation of their hosts worldwide. Several questions on their evolution, such as the phylogenetic position of Macrogyrodactylus and the highly speciose Gyrodactylus, remain unresolved with available mol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 108 publications
6
50
0
Order By: Relevance
“…In this study, we propose a NAD2 fragment as a specific marker for the common pandora. The gene NAD2 was previously investigated as a marker for population studies of plants, parasites and animals [ 22 , 23 , 24 , 25 ]. However, no use is made of this gene, as far as we know, in fish species identification against frauds, and our results show that its use warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we propose a NAD2 fragment as a specific marker for the common pandora. The gene NAD2 was previously investigated as a marker for population studies of plants, parasites and animals [ 22 , 23 , 24 , 25 ]. However, no use is made of this gene, as far as we know, in fish species identification against frauds, and our results show that its use warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…For colonial volvocine algae, previous studies have mainly focused on the conformation of mtDNA, and few have reported phylogenetic analyses based on mtDNA protein-coding genes in this group of algae. Phylogeny based on mtDNA has been widely used in different types of species, such as fish, parasites, brown algae, red algae, and green algae [8][9][10][11][12]. The phylogenetic analyses among colonial volvocine algae in previous studies were mainly based on genes such as the internal transcribed spacer (ITS), the large subunit of the ribulose-1,5-bisphosphate carboxylase/oxygenase (rbcL) gene, five chloroplast protein-coding genes, and the chloroplast genome [7,[13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Ofmentioning
confidence: 99%
“…The technique is potentially efficient for old museum material and ethanol-preserved specimens (Staats et al, 2013;Maddison and Cooper, 2014;Linard et al, 2016;Grandjean et al, 2017). Despite recent efforts to obtain DNA sequences through HTS protocols from museum specimens (McCormack et al, 2017;Dabney et al, 2013;McCormack et al, 2016) and ethanol material (do Amaral et al, 2015;Brabec et al, 2015Brabec et al, , 2016Hartikainen et al, 2016;Vanhove et al, 2018), the potential use of genome skimming for this purpose remains unexplored. There is a variety of suitable HTS sequencing platforms and library options to choose from to use in combination with genome skimming, including PCR-based libraries and PCR-free libraries that are less-error prone but require higher input DNA ( 1µg) (Twyford and Ness, 2017).…”
mentioning
confidence: 99%
“…Hence, it is not uncommon to find studies addressing phylogenetic relationships at different levels of divergence-including the interest on detecting cryptic species-based on these markers (von Nickisch-Rosenegk et al, 1999;Zehnder and Mariaux, 1999;Hu et al, 2005;Wickström et al, 2005;Littlewood et al, 2008;Brabec et al, 2016;Vanhove et al, 2018, to cite a few). However, to date HTS provided the means of sequencing the complete mitochondrial genome in reasonable time and at relative low cost.…”
mentioning
confidence: 99%
See 1 more Smart Citation